AUA SYMPTOM SCORE - A SIMPLE TOOL FOR ASSESSMENT OF BENIGN PROSTATIC HYPERPLASIA IN A RURAL SETTING - Patel, S P; Srivastava, V K (Indian Journal of Community Health, 2013)
Background: Benign Prostatic Hyperplasia (BPH) is one of the most common disease in ageing men and can be associated with Lower Urinary Tract Symptoms (LUTS) that affect quality of life by interfering with normal daily activities. The American Urological Association Symptoms Index (AUA-SI) is recommended as symptom scoring instrument to be used in initial assessment of each patient presenting with symptoms of prostatism. Objective: To assess the severity of symptoms in Benign Prostatic Hyperplasia subjects by using AUA symptom score in rural population of Lucknow, U.P. Materials and Methods: It is a rural community based cross-sectional study (2008-2009) conducted in the field practice area of Rural Health Training Centre (RHTC) of Community Medicine department, CSM Medical University UP, Lucknow. The study covered three villages by doing house to house survey. All males of 45 years and above were contacted and information regarding bio-social characteristics taken by using pre-tested questionnaire. Information regarding LUTS was gathered using AUA symptom score questionnaire. Data was analyzed using chi square test. Results:The prevalence of BPH amongst males aged 45 years and above in the rural area studied was 11.8%. The prevalence of BPH was maximum (62.5%) in the age group of 75 years and above. About 60% BPH patient aged > 75 years was found to have AUA symptom score of moderate grade (8to19), whereas only 25% BPH aged 45-54 years were having same grade of AUA symptom score. In the present study, out of 66 patients only 23 (34.8%) had moderate AUA symptom score and 43 had mild (1-7) AUA symptom score. No one had severe symptom score. Conclusions: Only 34.8% BPH cases were found to have moderate symptoms and awareness of prostate swelling seems to be much poor even after consultation. For proper management of subjects with moderate to severe symptoms, public health awareness campaigns and annual surgical camp must bearrange in rural area.